Complete AV Block in Vaccinated COVID-19 Patient. (30th March 2022) - Lee, Kevin; Rahimi, Osman; Gupta, Neelesh; Ahsan, Chowdhury
Abstract : Background . Coronavirus 2019 (COVID-19) was initially identified approximately in December 2019 at Wuhan, China, as patients presented with vague prodromal and respiratory symptoms. With the developing investigation of its clinical manifestation, cardiac symptoms have been widely reported including acute coronary syndromes, myocarditis, arrhythmias, heart failure, and cardiac arrest. Case Summary . An 84 year-old male with history of coronary artery disease, hypertension, and hyperlipidemia presented to an outside urgent care with prodromal symptoms. The patient had received the second Pfizer vaccine three months prior. This presentation, he was found to be COVID-19 positive as well as bradycardic with a complete AV block. He was transferred to a tertiary center for further evaluation and management. However, after transfer, the patient refused further invasive cardiac interventions and after medical therapy was discharged home in complete AV block. Discussion . We report a novel case of a Pfizer-vaccinated patient whose initial presenting symptoms of COVID-19 included a complete AV block as well as the challenges and difficulties in approaching such patients. Although this patient's etiology of his complete AV block may result from multiple factors, given the acuity in setting of concurrent COVID-19 infections, top differentials include viral myocarditis, COVID-19-induced Takotsubo cardiomyopathy complicated by a complete AV-block, or a direct conduction pathway infection. Management of patients should focus on a multidisciplinary approach, and prevention is critical via vaccination.